How microbial model systems help decipher cancer evolution Wie mikrobielle Modellsysteme helfen, Tumorevolution zu entschlüsseln - Eiche, Maximilian; Kayser, Jona (BioSpektrum, 2022)
While cellular evolution is one of the most fundamental concepts of life, its consequences are among the most pressing issues of modern health care, including cancer and the emergence of therapy resistance. We currently still lack the ability to accurately predict evolutionary trajectories, especially in spatially dense, pathogenic cellular populations such as microbial biofilms or solid tumors. Here, we discuss the conceptual framework of evolution in dense populations and the potential of tailored microbial model systems to systematically study the underlying mechanisms.
CRIS-Team Scopus Importer:2024-12-16